Supporting the delivery of good maternity care for parents with learning disabilities. (November 2021) - Cox, Anna; Parsons, Treena; Watkin, Scott; Gallagher, Ann
Abstract: Background and objective: Despite directives to improve maternity care in general and to improve care for parents with learning disabilities, the maternity experience of parents with learning disabilities is often poor and lacking reasonable adjustments to care. The objective of this study was to develop resources - in collaboration with key stakeholders - to support the workforce in delivering good maternity care to parents with learning disabilities. Design: A two-phase mixed-methods study. Participants: Phase 1: 16 key stakeholders (health and social care professionals, parents with learning disabilities and their informal supporters/carers) were interviewed to understand views of best practice and inform resource development. Phase 2: 20 healthcare professionals engaged with the resources and gave feedback via online survey or discussion group to further refine them. Findings: Thematic analysis of key stakeholder interviews indicated that good maternity care for parents with learning disabilities requires a positive and proactive approach to identifying need; reasonable adjustments to communication and providing information; and professionals working together to support and enable parents. Key conclusions: Health and social care professionals identified barriers to the delivery of good maternity care for parents with learning disabilities, including how to identify whether a parent has learning disabilities. Professionals in maternity services require additional resources to ensure parents' needs are recognised and they are provided with personalised preparation for parenthood and sufficient support. Implications for practice: The Together Toolkit and Maternity Passport were coproduced to support the workforce to deliver good maternity care to parents with learning disabilities, these resources are free and accessible for use [https://www.surrey.ac.uk/research-projects/together-project-supporting-delivery-good-practice-maternity-services-parents-learning-disabilities ]. Further evaluation will explore acceptability and perceived impact of these resources in maternity services.